A Note on Fractional Order Derivatives and Table of Fractional Derivatives of Some Special Functions - Atangana, Abdon; Secer, Aydin (HINDAWI LTD, 2013)
The purpose of this note is to present the different fractional order derivatives definition that are commonly used in the literature on one hand and to present a table of fractional order derivatives of some functions in Riemann-Liouville sense On other the hand. We present some advantages and disadvantages of these fractional derivatives. And finally we propose alternative fractional derivative definition.
Keywords: ANOMALOUS DIFFUSION; DIFFERENTIAL-OPERATORS; REGULARIZATION; EQUATIONS; Mathematics